Engineering of a monodisperse core-shell magnetic Ti-O-Si oxidation nanocatalyst. - Tang, H; Yu, C; Oduoro, W; He, H; Tsang, S (2008)
There has been limited development in catalyst carriers for magnetic separations where superparamagnetic nanoparticles of a high saturation magnetization with no coercivity are required to isolate expensive catalyst reagent that are subjected to repeated magnetic cycles. By using simple stepwise layer-by-layer nanochemistry techniques, we show that an fcc FePt nanomagnet can be created inside each silica particle with tailored dimensions to great precision. Subsequent engineering of the external surface with Ti-O-Si species in an optimum structure to create a unique interface gives high activity and excellent selectivity of the composite material for the trans-stilbene oxidation to the corresponding epoxide in the presence of tert-butyl hydroperoxide. Thus, a new magnetic separable epoxidation catalyst is described. This work clearly demonstrates the significance of nanoengineering of a single catalyst particle by a bottom-up construction approach in modern catalyst design, which could lead to new catalytic properties.